Strategy for Handling Pre-Disaster Floods Lere Sub-District Case Study - Fira Anisya Pettalolo; Mukafih, Ahmad Haqiq (Jurnal Teknik Sipil dan Perencanaan, 2024)
Lere Village is an area affected by flooding problems. The threat of disasters that routinely occur in Lere Village has harmed residential areas. Therefore, it is necessary to research pre-flood disaster management strategies. The research employed a qualitative approach with data collection methods based on primary and secondary data sources. Primary data was collected through field observations, documentation, and interviews with the community related to the management strategy before the flood. In contrast, secondary data is collected from the agency BPBD (Regional Disaster Management Agency), which is then processed to achieve research objectives. This study used a qualitative method, which was analyzed using a SWOT analysis. The results of this study indicate that eight alternative flood pre-disaster management strategies can be carried out: 1) Can build embankments along the Palu River. 2) Improving the flood control system in Palu Bay and Palu River. 3) It is hoped that the government will build floodgates to handle floods. 4) Optimization of the drainage system. 5) It is hoped that it can facilitate early warning tools at the point of flooding. 6) Directions for handling coastal border areas. 7). Directions for making houses on stilts for vulnerable areas, 8) Increased cooperation with various parties in handling Land subsidence for vulnerable areas, and Increasing cooperation parties in handling land subsidence.